Spy ships : one hundred years of intelligence collection by ships and submarines - Polmar, Norman; Mathers, Lee J. (Potomac Books, an imprint of the University of Nebraska Press, 2023)
Spy Ships highlights specialized naval ships used for collecting intelligence and reveals their major impact on military operations and national security.